Investigating the moderating effect of operational risk on the relationship between social responsibility and cost of equity capital in companies listed on Tehran stock exchange - Sotoudeh, Reza; Fard Tehran, Fereshteh Nami; Samet, Hossein (Nexo Revista Científica, 2022)
This study investigates the relationship between social responsibility and cost of equity capiral and the moderating effect of operational risk on the mentioned relationship. The study covers a 6-year research period during 2014 to 2019. 146 firms (total of 876 year-firm) are selected as the statistical sample using systematic elimination sampling method. The hypotheses are analyzed using multivariate regression models and panel data methods are also applied. The results indicate there is a significant negative relationship between social responsibility and cost of equity capital. The operational risk has a significant and inverse effect on the relationship between social responsibility and cost of equity capital.